A technical and economic assessment of grid-connected solar photovoltaic in the Philippines - Garcia, Jan Aaron Augustus F. (2012)
Solar Photovoltaic is the fastest growing energy technology in the world, with a year on year growth rate on installed capacity of 60% from 2006 to 2011. The price of crystalline solar photovoltaic modules has drastically dropped to about USD 1.5 per watt today, from over USD 4.5 per watt 5 years ago. Thin film technologies are currently being producers at less than USD 1.0 per watt. By 2011, over 60-GW of solar photovoltaic had been installed worldwide. This came with the rapid industrialization and scaling manufacturing capacities for solar PV technologies. Despite these opportunities, the Philippines through the Department of Energy has chosen to seek only a small quantity of energy from solar, based on the latest Philippine Energy Plan, and proposes feed-in tariff rates ar a time that most developed nations are already phasing it out for solar PV technology. This work aims to develop an understanding of solar PV within the Philippine context through the development of a two tiered life cycle assessment of the technology. The first tier is a macro analysis of the Philippine resource, matched by the definition of seventy-five technology configurations to identify best locations and best technologies for application. Five classifications of solar modules, three inverter types, and five mounting or tracking types were used in the analysis. The Life Cycle Analysis calculates for the net present value, return of investment, levelized cost of electricity, and metric defined in this work, the feasibility index for technology and economic assessment. The second tier involves the case study of a 40-KW and 2-MW project currently being undertaken by a private developer. The bottom up analysis from the case study serves as validation tool for the results of trhe first tier.The work shows that over the 25-year life of the solar PV modules, it costs only PHP 6.50 to PHP 8.0 today to produce solar PV electricity, depending on the particular technology configuration. The cheapest configuration is composed of Cadmium Telluride module technology, mounted on fixed tilt structures that can be adjusted seasonally, connected to large centralized inverters. This price can be expected to drop further if cost reductions follow the experience curve model used in the analysis. Cost reductions however are limited by installation cost increases. Installation costs increasingly become the dominant cost component, as opposed to the modules or inverters. This draws attention to the experience required in the installation of solar PV, where local learning is required to help address the installation costs issue, as opposed to module and inverter technology where learning is already global. This work concludes with a grid parity analysis of LCOE for the Philippine market, in which a redefinition of a grid parity is proposed. Financial viability is always the key decision driver in making any investment. As such, grid parity may not necessarily lead to the widespread deployment of solar PV as expected. The ratio of the investment required versus the capacity factor of the solar PV plant is restrictive to make a profit. Grid parity analysis shows that solar PV technology can only expect to achieve 10-15% return on investment selling at retail grid rates by 2020 to 2030 depending on the technologies used. The feasibility indices are then built into the Philippine Solar Photovoltaic Technology maps. The feasibility index is a measure of the quantity of energy that a particular technology configuration can produce at a particular location given the amount of solar resource there. The maps can be used as a preliminary reference to quantify the amount of energy a particular size and technology configuration of a power plant can produce. Solar photovoltaic is a new energy technology that can be taken advantage of by the Filipino people. Today, it has the capability to create energy cost savings against grid electricity with better performance than standard financial instruments over its 25-year life. This energy cost savings progressively improve, assuming experience curve scenarios, efficiency trends, and energy cost escalation rates are followed. It is imperative to understand the benefits of the technology and to create a market and industry to the country's economic and environmental benefit.